2024
DOI: 10.1094/pdis-06-23-1138-re
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Use of Quaternary Ammonium-Based Disinfectants in Biosafety Protocols Against Fusarium oxysporum f. sp. cubense Race 1 and Tropical Race 4

Laura Arango-Palacio,
Andrés M. Pinzón-Núñez,
Lilliana Hoyos-Carvajal
et al.

Abstract: The banana is one of Colombia's main export products. However, production is seriously affected by Fusarium wilt of Banana (FWB), which is the most destructive disease caused by the fungus Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4). Currently, management strategies focus on containment and biosecurity protocols to prevent its spread to territories that are free of this disease. This study aimed to evaluate 9 quaternary ammonium-based disinfectants (QAC) in vitro in Colombia on reproductive (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The effectiveness of disinfectants has been tested in numerous trials ( Table 2 ). Studies conducted without the presence of soil have shown that all Quaternary Ammonium Compounds (QACs) are effective against TR4 ( Nguyen et al., 2019 ; Izquierdo-García et al., 2021 ; Salacinas et al., 2022 ; Arango-Palacio et al., 2023 ). Notably, didecyl dimethyl ammonium chloride, 10%-30% (DDAC) and benzalkonium chloride 10% - 25% (BC) disinfectants at a 1% concentration were able to eliminate spores of both TR4 and R1 ( Nguyen et al., 2019 ).…”
Section: Management Options In the Context Of Latin American And The ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of disinfectants has been tested in numerous trials ( Table 2 ). Studies conducted without the presence of soil have shown that all Quaternary Ammonium Compounds (QACs) are effective against TR4 ( Nguyen et al., 2019 ; Izquierdo-García et al., 2021 ; Salacinas et al., 2022 ; Arango-Palacio et al., 2023 ). Notably, didecyl dimethyl ammonium chloride, 10%-30% (DDAC) and benzalkonium chloride 10% - 25% (BC) disinfectants at a 1% concentration were able to eliminate spores of both TR4 and R1 ( Nguyen et al., 2019 ).…”
Section: Management Options In the Context Of Latin American And The ...mentioning
confidence: 99%
“…More research is needed to identify affordable and effective disinfectants for the region. Studies with Foc R1, prevalent in many TR4-free countries, could serve as a model for pre-emptive research on disinfectants and other management measures ( Izquierdo-García et al., 2021 ; Arango-Palacio et al., 2023 ).…”
Section: Management Options In the Context Of Latin American And The ...mentioning
confidence: 99%